An Investigation of the Impact of Government Efficiency on Inflation Rate in Selected MENA Countries - Hassan Heidari; Rana Asghari; Roghayyeh Ali-Nezhad (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2015)
The present study investigates the impact of government efficiency on inflation rate with considerations on the relationship of this important index with government intervention in the economy and also with the structure of government expenditures for 16 countries from MENA region over the period 1996-2012. For this purpose, the paper uses the Panel Smooth Transition Regression (PSTR) model. The estimation results of model reject the linearity hypothesis, and estimate a continuous transition function with two regimes that gives a threshold at government efficiency of 0.185 for countries studied in this paper. Moreover the results indicate that government efficiency index, GDP growth and openness index have a negative impact on inflation rate that their impacts are increased for the values above the threshold calculated for government efficiency. The other results indicate that the coefficients of the government consumption expenditures growth and liquidity variables are positive and significant in two regimes. Though, their impacts are less in second regime. In general, the results of this study confirm the results of many other studies about positive effects of government consumption expenditure growth and liquidity and also negative effects of government efficiency index, GDP growth and openness index on inflation rate. Thus, it is recommended to reduce government size trough minimizing government personnel and its levels. It is also recommended to institutionalize accountability systems over the administrative and legal frame, and staffs professional manner in reception with citizens, and also have political stability and independence of government to central bank. These are effective ingredients in increasing the government efficiency and reduction of inflation rate.